Oxidation stability of confined linear carbon chains, carbon nanotubes, and graphene nanoribbons as 1D nanocarbons. Issue 32 (6th August 2019) - Cui, Weili; Saito, Takeshi; Ayala, Paola; Pichler, Thomas; Shi, Lei
Abstract : Three typical one-dimensional (1D)/quasi-1D nanocarbons, i.e. linear carbon chains, carbon nanotubes, and graphene nanoribbons, have been proved to be highly resistant to the oxidation due to the encapsulation inside single-walled carbon nanotubes. Abstract : Three typical one-dimensional (1D)/quasi-1D nanocarbons, linear carbon chains, carbon nanotubes, and graphene nanoribbons have been proved to grow inside single-walled carbon nanotubes. This gives rise to three types of hybrid materials whose behaviour and properties compared among each other are far from being understood. After proving the successful synthesis of these nanostructured materials in recently published work, we have now been able to study their oxidation stability systematically by using resonance Raman spectroscopy. Surprisingly, the linear carbon chains, which have been theoretically predicted to be very unstable, are actually thermally stable up to 500 °C, assisted by the protection of the carbon nanotube hosts. Besides, longer linear carbon chains inside narrower CNTs are more stable than the shorter ones inside larger tubes, suggesting that the thermal stability not only depends on the length of linear carbon chains alone, but it is correlated with the confinement of the host tubes in a more complicated manner. In addition, graphene nanoribbons overall appear to be the most stable confined structures. On the other hand, peculiarities like the higher stability of the (6, 5) CNT compared to that of its (6, 4) counterpart allow this study to provide a solid platform for further studies on the application of these 1D nanocarbons (including true 1D linear carbon chains) under ambient conditions.